Valorisation of residues from municipal wastewater sieving through anaerobic (co-)digestion with biological sludge. Issue 6 (June 2022) - Boni, Maria Rosaria; Polettini, Alessandra; Pomi, Raffaella; Rossi, Andreina; Filippi, Alessandro; Cecchini, Giancarlo; Frugis, Alessandro; Leoni, Simone
The Circular and Green Economy principles is inspiring new approaches to municipal wastewater treatment plants (MWWTPs) design and operation. Recently, an ever-growing interest is devoted to exploring the alternatives for switching the WWTPs from being able to 'simply' removing contaminants from water to biorefinery-like plants where energy and material can be recovered. In this perspective, both wastewater and residues from process can be valorised for recovering nutrients (N and P), producing value added products (i.e. biopolymers), energy vectors and biofuels (i.e. bio-H2, bio-CH4 and bioethanol). As an additional benefit, changing the approach for WWTPs design and operation will decrease the overall amount of landfilled residues. In this context, the present research is aimed at evaluating the CH4 production potential of MWW screening units' residues. While such a stream is typically landfilled, the expected progressive increase of biodegradable matter content due to the ban on single-use plastic along with the boost of bioplastics makes the investigation of different biochemical valorisation routes more and more interesting from an environmental and economical perspective. Thus, a full-scale data collection campaign was performed to gain information on screening residues amount and properties and to analyse the relationship with influent flowrate. The most relevant residue properties were measured, and lab-scale tests were carried out to evaluate the bio-CH4 potential.